High-responsivity turbostratic stacked graphene photodetectors using enhanced photogating. (12th November 2019) - Shimatani, Masaaki; Yamada, Naoki; Fukushima, Shoichiro; Okuda, Satoshi; Ogawa, Shinpei; Ikuta, Takashi; Maehashi, Kenzo
Abstract: High-responsivity graphene photodetectors were fabricated using turbostratic stacked graphene, which provided enhanced photogating. Photogating is a promising means of increasing the responsivity of graphene photodetectors, and this effect is proportional to carrier mobility. Turbostratic stacked graphene exhibits higher carrier mobility than conventional monolayer graphene because it has the same band structure as monolayer graphene while preventing scattering by the underlying SiO2 layer. The photoresponse of these devices at a wavelength of 642 nm was approximately twice that obtained for a conventional monolayer graphene photodetector. The results reported show the feasibility of producing high-responsivity graphene-based photodetectors using a simple fabrication technique.